Examining Psychosociocultural Influences as Predictors of Black College Students' Academic Self-Concept and Achievement. (March 2021) - Beasley, Samuel T.; McClain, Shannon
Using the psychosociocultural framework, this study concurrently examined the influence of psychological (academic self-concept and academic engagement attitudes), social (caring student-faculty relationships), and cultural variables (racial centrality and perceived university environment) on the academic achievement of Black college students. Participants were 247 Black collegians recruited from a large, Southwestern predominately White institution. Results of structural equation modeling largely supported hypothesized relationships between variables, accounting for 16% of the variance in grade point average (GPA), 75% of the variance in academic engagement, and 29% of the variance in academic self-concept. Results revealed two positive direct paths to GPA: (a) racial centrality and (b) academic self-concept; academic self-concept had a key role in facilitating indirect effects on academic engagement and GPA. Findings highlight multiple noncognitive predictors that can facilitate Black students' academic functioning. Research and practice implications of these findings are outlined.